Dairy contract farming in Bangladesh: Implications for welfare and food safety - Islam, Abu Hayat Md. Saiful; Roy, Devesh; Kumar, Anjani; Tripathi, Gaurav; Joshi, Pramod Kumar (International Food Policy Research Institute, 2019)
Contract farming is emerging as an important institutional innovation in the high value food chain in developing countries including Bangladesh, and its socioeconomic implications are topic of interest in policy debates. This study is an empirical assessment to explore the determinants of participation and the impact of contract farming on welfare and adoption of food safety practice in Bangladesh. Our analysis indicates that contract farmers are more likely to have better access to agricultural extension services, attended proportionately more community meetings, households members are member of organizations, access more credit, are located farther from output market, and have larger herd sizes. We also find that network variables such as time spent with cooperatives and other institutions and price fluctuation and average prices received experience before participation in contract are strongly associated with participation in contract farming. We find that contract farming has a robust positive impact on welfare measured by expenditure, farm profit and farm productivity, and food safety practice adoption even after innovatively controlling for observed and unobserved heterogeneity among dairy farmers. More specifically results indicate that a one unit increase in the likelihood of participating in contract farming is associated with a 42, 35,34 and 9 percent increase in household expenditure, gross margin and net margin per cow, and food safety practice adoption rate respectively, among other positive impacts.